Analisis Keandalan Transformator Daya 70/20 KV Di PT.PLN (Persero) P3BS GI Sukamerindu Berdasarkan Hasil Pengujian Isolasi Minyak DGA (Dissolved Gas Analysis) Menggunakan Metode Markov - Afrizon, Hergo; Firdaus, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Power transformer plays a very important role in the electric transmission system to convert the voltage level of the system. An abnormal operation of power transformer can decrease its reliability. The most common cause of abnormal operation in power transformer is oil damage. Markov method is applied using Dissolved Gas Analysis (DGA) test from transformer oil to determine transformer’s insulation resistance and breakdown voltage. Continuous Markov method is applied to determine steady-state and inntantaneous conditions that occur in the transformer’s oil. Furthermore, Markov process the power transformer must satisfy certain requirements such as lack of memory and stationery or homogeny. After all requirements are met, then the value of each transfer rates and transition times are determined for transformer reliability and availability calculations transition matrix by using rate of failure (λ), rate of improvement (μ), the stead-state value of transition matrix. The sum of all incident condition value, failure rate and rate of improvement are considered as transformer reliability. The result of Markov continuous analysis obtained the transformer reliability for total Dissolved Combustible Gases (TDCG) parameter for initial operation is 0.99 and it decreased to 0.60 after 365 days of operation. The transformer reliability decreased to 39% for 365 days of operation. Furthermore, the transformer availability for duriation of 302 days are considered as good condition for all TDCG gas parameter and not good for 61 days.Keywords : Oil Testing Transformer DGA (Dissolved Gas Analysis), Isolation Resistance and Breakdown Voltage, Markov Continuous Method.